Comparison of Vitamin D3 Supplementation Doses of 1,000, 2,000, 4,000 and 8,000 IU in Young Healthy Individuals - Kralova, Marketa; Jirasko, Michal; Dedeckova, Eva; Hatakova, Hedvika; Broz, Pavel; Simanek, Vaclav; Slouka, David; Pecen, Ladislav; Kucera, Radek (In vivo (Athens, Greece), 2025)
BACKGROUND/AIM: Low levels of vitamin D are a widespread global issue. This study aimed to determine the optimal vitamin D3 supplementation dose for healthy young adults by comparing the effectiveness of gradually increasing cholecalciferol doses over two years. PATIENTS AND METHODS: Thirty-five volunteers participated in a two-season pilot study conducted from October to April to avoid sunlight-induced vitamin D3 synthesis. The participants used oil-based drops of cholecalciferol, increasing their dose from 1,000 to 2,000, 4,000, and then 8,000 IU daily for 60 days with a 30-day break. RESULTS: Supplementing with 1,000 IU/day raised vitamin D levels to the recommended range (above 75 nmol/l), but levels dropped below this range after a 30-day break. A dose of 2,000 IU/day maintained vitamin D levels within the recommended range, even after the break. Increasing the dose to 4,000 IU/day produced a rapid rise, though levels dropped more significantly after stopping supplementation. With 8,000 IU/day, both the rise and subsequent decline in vitamin D levels were more pronounced. CONCLUSION: Effective vitamin D supplementation in healthy young adults can be achieved with a daily dose of 2,000 IU during winter. However, 4,000 IU/day was more effective for maintaining levels above 100 nmol/l, supporting broader health benefits. Regular monitoring of [25(OH)D], calcium, and phosphorus levels is essential.
Keywords: Pilot Projects; potravní doplňky; Vitamin D Deficiency; vitamin D deficiency; Cholecalciferol; Adult; supplementation; Male; roční období; lidé; Humans; Seasons; supplementation safety; Healthy Volunteers; Young Adult; Dose-Response Relationship, Drug; supplementation dose; [25(OH)D)]; pilotní projekty; mužské pohlaví; Vitamin D; dospělí; mladý dospělý; cholekalciferol; zdraví dobrovolníci pro lékařské studie; ženské pohlaví; vztah mezi dávkou a účinkem léčiva; Female; vitamin D; nedostatek vitaminu D; Dietary Supplements